Anthropometric Profile of Malaysian Sport School Council Netball Players Under 18 Years Old - Osman, Noorzaliza (2008)
The aims of this study were to determine overall profile and anthropometry differences within the netball players (PBJ) of the Malaysian Sport School Council (MSSC) 2006 based on player position and team performance. The measurement variables were height, weight, body fat percentage and somatotype. One-hundred and fifty netball players representing 13 states and two federal territories were involved. They were divided into playing position (defence, attack and centre) and team performance (high and low). A body fat percentage was measured by skinfold method based on Jackson, Pollock & Ward (1980) formula and somatotype using the Heath and Carter method (2002). One- way MANOVA test used to anaylize the data. Significant result were reported for height and body weight based on the playing position. The F value showed for height and body weight was F (2,147)=43.42, p<0.05 dan F (2, 147)=15.30, p<0.05 respectively. The overall result showed that MSSM netball players had the same height and body weight with Malaysian netball players. Whereas, body fat percentage for MSSM netball players also lower than Malaysian netball players reported by Soh (2005). The players had endomorphic-mesomorphic bodies (more muscular), as was also studied by Hopper, Hopper & Elliot (1995) for Australian players. From this study, it can be concluded that MSSM 2006 netball players had the same physical profile with elite players in Malaysia and other countries.